2020
DOI: 10.31235/osf.io/a8r3p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Right-Leaning Media Coverage of COVID-19 Facilitated the Spread of Misinformation in the Early Stages of the Pandemic

Abstract: In recent weeks, several academic and journalistic outlets have documented widespread misinformation about the origins and potential treatment for COVID-19. This misinformation could have important public health consequences if misinformed people are less likely to heed the advice of public health experts. While some have anecdotally tied the prevalence of misinformation to misleading or inaccurate media coverage of the pandemic in its early stages, few have rigorously tested this claim empirically. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 0 publications
2
104
0
2
Order By: Relevance
“…they focus other explanatory factors and thus only include age to obtain more precise estimates) and do not discuss its implications. [11][12] In other words, the majority of research does not include age as having a potentially non-linear effect on different variables related to COVID-19.…”
Section: Plos Onementioning
confidence: 99%
“…they focus other explanatory factors and thus only include age to obtain more precise estimates) and do not discuss its implications. [11][12] In other words, the majority of research does not include age as having a potentially non-linear effect on different variables related to COVID-19.…”
Section: Plos Onementioning
confidence: 99%
“…Previous research has indicated that exposure to certain media outlets (particularly Fox News) contributes to politically relevant outcomes (DellaVigna and Kaplan 2007;Feldman et al 2012); new research similarly suggests coronavirus-related mediasource effects. For instance, Matt Motta, Dominik Stecula, and Christina Farhart (2020) found that right-leaning news sources (Fox News, Breitbart) were more likely than others to disseminate specific pieces of misinformation (e.g., that coronavirus is a conspiracy or was made in a lab), and that survey respondents who consumed more right-leaning news were also more likely to endorse misinformation. Similarly, Kathleen Hall Jamieson and Dolores Albarracin (2020) identified associations between exposure to mainstream broadcast news and the correct belief that COVID-19 is more lethal than the flu, exposure to mainstream print news and more accurate beliefs about infection prevention, and exposure to Fox News and Rush Limbaugh and more endorsement of conspiracy beliefs (that the CDC is exaggerating to undermine President Trump).…”
Section: Past and Emerging Research On Media Messaging And Its Effectmentioning
confidence: 99%
“…Although it has been documented that the political inclinations and associated media use of US residents predict their risk perceptions and worry about getting COVID-19 (Dryhurst et al 2020;Motta et al 2020), less is known about their contribution to risk perceptions for experiencing negative economic consequences during the pandemic, their preferences for the timing of opening the economy, and their tendencies to implement protective behaviors. Before the COVID-19 pandemic, a majority of US residents across the political spectrum viewed individuals as personally responsible for their own protective health behaviors to mitigate their health risks (Robert and Booske 2011).…”
Section: Introductionmentioning
confidence: 99%